Enterprise systems engineering : advances in the theory and practice - Rebovich, George; White, Brian E. (Taylor & Francis, 2016)
This new systems thinking is emerging at the intersection of seminal ideas from modern system thinkers, the broad discipline of information technology, and the theory of complex adaptive systems, particularly those from ecology and social systems. Part of this new system thinking requires a replacement of the notion that specific engineering outcomes or goals can always be assured with one that seeks to shape, improve, or increase the value of engineering outcomes through thoughtful interventions in the ever-increasing numbers of circumstances in which we are not fully in control. This book introduces and examines new and emerging modes of thought increasingly recognized as essential to successful systems engineering in enterprises.- Resumé vydavatel
Keywords: systémové inženýrství; podnikové informační systémy; systems engineering; management information systems; kolektivní monografie; elektronické knihy; collective monographs; electronic books